التربية الأسرية الديمقراطية ومستوى النمو الأخلاقي لطفل الروضة "دراسة ميدانية في رياض الأطفال بمحافظة اللاذقية الفئة الثانية " - الشماس, عيسى; حمدي, لميس (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف هذا البحث إلى تقصي العلاقة بين التربية الأسرية الديمقراطية في الأسر التي لديها أطفال في عمر الفئة الثانية أي (5-4) سنوات بمؤسسات رياض الأطفال في محافظة اللاذقية، ومستوى نمو السلوكات الأخلاقية لدى هذه الفئة من الأطفال. ولتحقيق أغراض البحث صممت الباحثة أداة الدراسة "استبانة", وطبقتها على عينتين مختارتين عشوائياً, إحداهما مؤلفة من (520) والداً ووالدة, منهم: (290) أباً, و(230) أما؛ والأخرى مؤلفة من (520) طفلاً وطفلةً. وطُبّق مقياس التفكير الأخلاقي المصور على الأطفال للدكتورة فوقية عبد الفتاح بعد أن عدّلته الباحثة, وحكّمته. وقد انتهى البحث إلى النتائج الآتية: 1- هناك علاقة ذات دلالة إحصائية بين الأسلوب الديمقراطي للأسرة, ومستوى النمو الأخلاقي للطفل. 2- هناك علاقة ذات دلالة إحصائية بين مستوى تعليم الآباء, ومستوى النمو الأخلاقي للطفل. 3- هناك علاقة ذات دلالة إحصائية بين مستوى تعليم الأمهات, ومستوى النمو الأخلاقي للطفل. This research aims to investigate the correlation between the democratic family method and the level of the ethical growth of the child within the families which have children at the age of the second section (4-5) years at the kindergartens in Lattakia. The researcher designed the tool of the study (a questionnaire) and applied it on a randomly chosen sample, which consisted of (520 ) parents. This sample was distributed into (290) fathers and (230) mothers, and another tool was applied, the ethical imaginative thinking scale for Dr. Faukia Abd Al Fattah, to measure the ethical thought of the kindergarten children after qualifying it by the researcher to match the children's ethical behaviors at this age; the children were(520) from the kindergartens in Lattakia. The research's results were: 1-There is a significant statistical correlation between the democratic family method and the level of the ethical growth of the child. 2-There is a significant statistical correlation between the level of fathers' education and the level of the ethical growth of the child. 3-There is a significant statistical correlation between the level of mothers' education and the level of the ethical growth of the child.